Reconceptualising Learning in the Digital Age The [Un]democratising Potential of MOOCs - Littlejohn, Allison (SpringerBriefs in Open and Distance Education,, 2018)
This book situates Massive Open Online Courses and open learning within a broader educational, economic and social context. It raises questions regarding whether Massive Open Online Courses effectively address demands to open up access to education by triggering a new education order, or merely represent reactionary and unimaginative responses to those demands. It offers a fresh perspective on how we conceptualise learners and learning, teachers and teaching, accreditation and quality, and how these dimensions fit within the emerging landscape of new forms of open learning.